Digital entrepreneurship : an 'idea bank' for local policymakers /: an 'idea bank' for local policymakers. (2016) - (Business research director), Haley, Christopher; Bannerjee, Siddharth; Bielli, Simona; (Quantitative researcher), Bone, Jonathan; Finger, Yann
No abstract available